Gambaran Konsep Diri Remaja Pengguna Aplikasi Tiktok di Kota Lamongan - Maryam Maryam (Muqoddima Jurnal Pemikiran dan Riset Sosiologi, 2022)
Tiktok application user are increasing every year, as are the features in it. The application is popular with various groups, especially teenagers. This study is intended to descraibe the self-concept of adolescent user of the Tiktok application in the city of Lamongan. This study uses a qualitative method with a descriptive from, then uses a purpose sampling data collection technique with a total of four active teenage participans using the Tiktok. Application in the city of Lamongan. The theory used in this study is the Hurlock’s self-concept theory, using several indicators of factors that influence the growth of self-concept in adolescents. Data collection was carried out by means of interviews, observations, and documentation, while the results of the findings in the field were then processed using data processing methods from Lexy J Moleng. The results of this study indicate that adolescent users of the Tiktok application in lamongan city have a positive self-concept. Keywords : Self-concept, Teenagers, Tiktok application.